(De)Constructing Physical Education through contemporary art learning environments (Agora for Physical Education and Sport, 2018)
The aim of this paper is to show how the learning conditions during the initial primary education teacher training studies at the Faculty of Education, Psychology and Social Work (Lleida-Spain) has allowed me to design and develop a teaching model based on a Physical Education around contemporary art environments. In order to analyze an inclusive, interdisciplinary and creative Physical Education program carried out in the Prince of Viana school of Lleida, our main methodological tools were  the autobiographical stories and field-notes, the audio and videotaping of the polyphony of pupils’ voices, and the pictures taken during the sessions.
Keywords: Physical Education; contemporary art; learning environments; interdisciplinary work; autobiographical story; students’ voices